The Impact of Sustainable Business Models on Social and Environmental Value Creation: A Cross-Industry Analysis - Ahmad Rofiq; Primadhani Dyah Larasati Suyatno; Maulana Ihsan Yusufi Suyatno (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2025)
This study explores the transformative potential of sustainable business models (SBMs) in driving social and environmental value creation across industries. Employing a mixed-method approach, the research integrates qualitative interviews with 30 key informants and quantitative analysis of industry-specific data to provide comprehensive insights. The findings reveal that implementing SBMs leads to significant reductions in carbon emissions, improved resource efficiency, and enhanced stakeholder engagement. Key enablers include the adoption of circular economy principles and collaborative stakeholder strategies, while challenges such as regulatory inconsistencies and high initial investment costs persist. The results align with theoretical frameworks like the Triple Bottom Line and Resource-Based View, emphasizing the need for balanced economic, social, and environmental outcomes. This study concludes by offering actionable recommendations for policymakers and business leaders, including fostering inclusivity, enhancing policy clarity, and promoting innovation to overcome barriers. The findings contribute to advancing knowledge on sustainable practices and supporting global sustainability initiatives.